Three-dimensional stability analysis of an urban slope located in João Monlevade, Brazil (Research, Society and Development, 2019)
Geotechnical stability analysis of slopes is an important tool for decision making in civil projects.  Use of three-dimensional software for analysis of soil slope stability has increased in recent years. Rocscience Inc. created Slide3 software in 2017. Slide3 is a software that allows geotechnical engineers to calculate the factor of safety of complex 3D slope stability geometries that 2D models cannot fully simulate. In this context, this paper presents a three-dimensional stability analysis of a slope located in an urban area at city of João Monlevade, Minas Gerais, Brazil. The slope was selected due to the instability history in rainfall periods. Topography of the area was provided by the city council. Young and mature residual soils were identified in the studied slope. Young residual soil was physically classified as clay without gravels and presents in natura values of cohesion and friction angle, equal to 32 KPa and 23.97º, respectively. Mature residual soil was physically classified as clayey silt without gravels and presents in natura values of cohesion and friction angle, equal to 19 KPa and 23.30º, respectively. The factor of safety of the soil slope was equal 0.977, considering the slope saturated. The factor of safety of the drained slope was equal to 1.415. Generalized limit equilibrium (GLE) method was used in this equilibrium-limit analysis.  The results stability analysis of the slope was coherent, once previous instability occurs in a period that was identified above average rainfall.